A fluid inclusion study of diagenetic fluids in Proterozoic and Paleozoic carbonate rocks, Victoria Island, NWT. Issue 4 (16th September 2013) - Mathieu, J.; Kontak, D. J.; Turner, E. C.
Abstract: Despite the presence of known economic resources in Canada's Arctic archipelago, Victoria Island remains understudied. This study addresses the fluid history and economic potential of two major carbonate units on Victoria Island by integrating fluid inclusion microthermometry with SEM‐EDS analysis of evaporate mounds. Three cements containing fluid inclusion assemblages (FIA) occur in the Neoproterozoic Wynniatt Formation: saddle dolomite, brown dolomite and calcite, in paragenetic order. The two dolomite‐hosted cements have average homogenisation temperatures ( T h ) for FIAs ( n  = 3) of 108°C (saddle) and 101 and 116°C, but metastability precluded determining salinities; most calcite‐hosted fluid inclusions are too small and/or necked to obtain T h values, but rare larger inclusions have salinities from 1.7 to 0.4 wt. % NaCl equiv. SEM‐EDS analysis of evaporate mounds indicates the fluid changed from an early K‐rich (saddle dolomite), to a later K + Na (brown dolomite), and finally Na‐rich (calcite), which suggests mixing of two end‐member fluids (i.e. Na‐rich and K‐rich). Dolostone of the lower Paleozoic 'Victoria Island formation' contains two cements: early quartz and late dolomite. Quartz‐hosted FIAs ( n  = 2) have an average T h value of 126°C, and salinity of 23.2 wt. % NaCl equiv., whereas FIAs ( n  = 3) in dolomite have average T h values of 109, 116 and 124°C; metastability precluded determining salinity. Evaporate mound analysis for the cements indicates evolution from a Na‐rich to a Na + K fluid through interaction with reservoir rocks. A reduced, metal‐rich fluid was present during quartz precipitation, as implied by the presence of pyrite framboids along growth zones and nanoparticles of barite and sulphide minerals (Zn, Cu and Pb) in evacuated inclusions, which suggests the area may have potential to host base‐metal mineralisation. Importantly, distinguishing different fluid compositions in both of the case studies would not have been possible without evaporate mound analysis and therefore the results emphasise integrating this technique into diagenetic studies. Abstract : Diagenetic fluids for two major carbonate units on Victoria Island have compositions that indicate mixing of multiple fluids and/or interaction with reservoir rocks. The utility of integrating the SEM‐EDS analysis on evaporate mounds is demonstrated to be effective in characterising fluid chemistry beyond standard microthermometry methods, particularly with metastable or small fluid inclusions. Metal‐rich fluids were present during cement precipitation, as indicated by nanoparticles in evacuated fluid inclusions, and therefore the possibility of economic potential exists in this area.